Viral Loads Anthropologies of urgency in the time of COVID-19 - Manderson, Lenore; Burke, Nancy J.; Wahlberg, Ayo (Embodying Inequalities: Perspectives from Medical Anthropology, 2021)
Drawing upon the empirical scholarship and research expertise of contributors from all settled continents and from diverse life settings and economies, Viral Loads illustrates how the COVID-19 pandemic, and responses to it, lay bare and load onto people's lived realities in countries around the world. A crosscutting theme pertains to how social unevenness and gross economic disparities are shaping global and local responses to the pandemic, and illustrate the effects of both the virus and efforts to contain it in ways that amplify these inequalities. At the same time, the contributions highlight the nature of contemporary social life, including virtual communication, the nature of communities, neoliberalism and contemporary political economies, and the shifting nature of nation states and the role of government. Over half of the world's population has been affected by restrictions of movement, with physical distancing requirements and self-isolation recommendations impacting profoundly on everyday life but also on the economy, resulting also, in turn, with dramatic shifts in the economy and in mass unemployment. By reflecting on how the pandemic has interrupted daily lives, state infrastructures and healthcare systems, the contributing authors in this volume mobilise anthropological theories and concepts to locate the pandemic in a highly connected and exceedingly unequal world. The book is ambitious in its scope - spanning the entire globe - and daring in its insistence that medical anthropology must be a part of the growing calls to build a new world.